Intrapulmonary shunting in the biliary atresia/polysplenia syndrome: reversal after liver transplantation. Issue 6 (June 1994) - Fewtrell, M S; Noble-Jamieson, G; Revell, S; Valente, J; Friend, P; Johnston, P; Rasmussen, A; Jamieson, N; Calne, R Y; Barnes, N D
Abstract : One hundred and seventy three children, including 93 with biliary atresia, received liver grafts at Addenbrooke's Hospital between 1983 and 1993. Of these, only seven developed cyanosis due to intrapulmonary shunting as a complication of their liver disease, and all seven of these had the biliary atresia/polysplenia syndrome. Intrapulmonary shunting was confirmed by a radioisotope scan in four children. Only one child with the syndrome did not have cyanosis when undergoing transplantation. Seven of the eight children are alive 6-54 months after transplantation, with normal pulmonary and hepatic function. Cyanosis recurred in one child who developed chronic rejection with liver failure. In conclusion: (a) there is a strong association between the biliary atresia/polysplenia syndrome and cyanosis due to intrapulmonary shunting; (b) intrapulmonary shunting is fully reversible after successful liver transplantation; and (c) cyanosis, once present, is progressive, and these children should be considered for liver transplantation as soon as it occurs.